Unveiling Characters in the Legend of Mon Seuribèe: A Study of Characterization - Qutteni, Dara; Iba Harliyana; Wulanda (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the characteristics of the characters in the legend of Mon Seuribèe originating from Parang IX, Matangkuli District, Aceh Utara Regency. By using a descriptive qualitative approach, this study identifies and describes the roles and characters possessed by each character. Research data were collected through recording techniques, focusing on sentences and paragraphs in the legend of Mon Seuribèe that contain elements of character and characterization. The results of the study show that the roles of characters in the legend of Mon Seuribèe are divided into main characters and supporting characters. Teungku Muhammad Syah Sabi (Teungku Batee Puteh) is identified as the main character with a responsible, religious, polite, honest character. Meanwhile, the supporting characters include Princess Amrah, who has a patient, loyal, and motherly character; Teungku Batèe Putéh's younger sister who is understanding and stubborn; King Lipah who is described as an understanding, confident, and loving figure; and residents who have a caring character and uphold the attitude of mutual cooperation. The techniques used are dramatic techniques and expository techniques.